Pitfalls in breast ultrasound (Nepalese Journal of Radiology, 2021)
The pitfalls associated with breast sonography are important to recognize because these may prompt biopsy of a benign lesion or result in failure to recognize a breast cancer.. The important categories of pitfalls are anatomical, technical and professional. The true cause of pseudo lesions is more evident at real time imaging. Appropriate machine setting, knowledge of breast anatomy and scanning in two planes is essential.